1978
DOI: 10.1177/014616727800400118
|View full text |Cite
|
Sign up to set email alerts
|

Buying Kindness: Effect of an Extrinsic Incentive for Helping on Perceived Altruism

Abstract: Two experiments were conducted to determine whether an extrinsic incentive would undermine intrinsic, altruistic motivation for helping. In Experiment 1 male undergraduates agreed to help an experimenter code data. Pavment for coding was not mentioned (no-payment), was mentioned prior to agreement to help (paynent-prior), or was mentioned after agreement to help (payment-after). As predicted from Nisbett and Valins' overly sufficient justification hypothesis, subjects in the payment-prior condition rated thems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 8 publications
3
51
0
Order By: Relevance
“…Studies of volunteerism and altruistic behavior in a variety of contexts have demonstrated that external social pressures to help others can undermine intrinsic commitment to help, and cause volunteers to discontinue their participation sooner, or at higher rates than volunteers who did not experience such pressures. [11][12][13] We also expected that, in addition to the conditions under which individuals joined the registry, their stated motives for joining would also be associated with the likelihood they would drop out of the registry later. Previous research has demonstrated that motives are related to continued volunteerism or to feelings about participation in volunteer activities among volunteer 'buddies' for AIDS patients, 14,15 4-H volunteers, 16 social service volunteers, 17 elderly volunteers, 18 kidney donors 4,19 and bone marrow donors.…”
Section: Recruitment Issuesmentioning
confidence: 99%
“…Studies of volunteerism and altruistic behavior in a variety of contexts have demonstrated that external social pressures to help others can undermine intrinsic commitment to help, and cause volunteers to discontinue their participation sooner, or at higher rates than volunteers who did not experience such pressures. [11][12][13] We also expected that, in addition to the conditions under which individuals joined the registry, their stated motives for joining would also be associated with the likelihood they would drop out of the registry later. Previous research has demonstrated that motives are related to continued volunteerism or to feelings about participation in volunteer activities among volunteer 'buddies' for AIDS patients, 14,15 4-H volunteers, 16 social service volunteers, 17 elderly volunteers, 18 kidney donors 4,19 and bone marrow donors.…”
Section: Recruitment Issuesmentioning
confidence: 99%
“…Still, two experiments have successfully demonstrated that extrinsic incentives for help giving can lead helpers to describe themselves as less altruistically motivated. During the course of an experiment on "first impressions," Batson, Coke, Jasnoski, and Hanson (1978) asked male undergraduates to help an experimenter code data. Payment for this help was offered before subjects agreed to help (payment condition), after the subjects' agreement (payment after), or payment was not mentioned at all (no payment).…”
Section: Measurement Of Altered Self-perceptionsmentioning
confidence: 99%
“…The introduction of a monetary reward for performing a task which subjects originally regarded as intrinsically enjoyable consistently reduced the intrinsic pleasure subjects reported deriving from the task and, furthermore, reduced their rate of volunteering to repeat the experiment. (Deci, 1975;Notz, 1975;Staw, 1975) Batson et al (1978) confirm that this general principle applies in the case of moral motives. "Buying kindness," the offer of monetary rewards for helping others with a task, reduced the subjects' self-reported altruism [6].…”
Section: ) Patriotic Duo'mentioning
confidence: 91%
“…6 Social psychologists ordinarily explain these results somewhat implausibly in terms of"attribution theory". Batson et al ( 1978), for example, suppose that where altruism also pays subjects simply tend to attribute their behaviour to the baser motive: the introduction of an extrinsic reward has not made people worse, really; it has only confused them about their own motives. But when there are both altruistic and egoistic reasons for an action, why should subjects always attribute the choice to the egoistic motive?…”
Section: Notesmentioning
confidence: 99%